Polycarbonate urethane nanocomposites with nanosilica for implants of the intervertebral disc - Waśniewski, B.; Auguścik, M.; Parzuchowski, P.; Zielecka, M.; Ryszkowska, J. (Polimery, 2012)
Two types of nanocomposites with polycarbonate urethane (PUR) matrix were made in order to obtain an elastic material intended for the implant of intervertebral disc. Oligocarbonate diols of different molar masses (1534 g/mol and 1750 g/mol) were used for the synthesis. Each of the composites contained 0.5 wt. % silica with an average nanoparticle size of 57 nm. The produced materials were characterized for strength properties and investigated by thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) and dynamic mechanical analysis (DMA). The chemical structure of the produced nanocomposites was confirmed on the basis of Fourier transform infrared spectroscopy (FT-IR), while the adhesive properties were evaluated by contact angle measurements.